2018
DOI: 10.1080/14786419.2018.1517120
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity evaluation of thiourea derivatives bearing Salix sp. constituent against HK-1 cell lines

Abstract: In searching for drugs from natural product scaffolds has gained interest among researchers. In this study, a series of twelve halogenated thiourea (ATX 1-12) via chemical modification of aspirin (a natural product derivative) and evaluated for cytotoxic activity against nasopharyngeal carcinoma (NPC) cell lines, HK-1 via MTS-based colorimetric assay. The cytotoxicity studies demonstrated that halogens at meta position of ATX showed promising activity against HK-1 cells (IC 50 value 15 mM) in comparison to cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This inhibitory effect has two main aspects: inhibiting cancer cell proliferation and promoting cancer cell apoptosis (45)(46)(47). Recent studies have shown inhibitory effects on the expansion of human acute promyelocytic leukemia cells and K562 cells (48), Bel-7402 cells (49), human breast cancer cells (50,51), and nasopharyngeal carcinoma HK -1 cells (27). We expected that both DMY and MYT would have inhibitory effects on B16F10 cells.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This inhibitory effect has two main aspects: inhibiting cancer cell proliferation and promoting cancer cell apoptosis (45)(46)(47). Recent studies have shown inhibitory effects on the expansion of human acute promyelocytic leukemia cells and K562 cells (48), Bel-7402 cells (49), human breast cancer cells (50,51), and nasopharyngeal carcinoma HK -1 cells (27). We expected that both DMY and MYT would have inhibitory effects on B16F10 cells.…”
Section: Discussionmentioning
confidence: 94%
“…After treatment for 72 h, 10 µL of 5 mg/mL MTT was added to each well. The media containing MTT was removed after 4 h, and 100 µL DMSO was added to each well to dissolve the formazan crystals (27). The plate was shaken for 1 min, the absorbance at 490 nm was measured, the inhibition rate of the drug on cell growth was calculated, and the general equation for the dose-effect relationship was obtained according to the following formula.…”
Section: The Proliferation Of B16f10 Cells By Mtt Assaymentioning
confidence: 99%
“…Hybridization of azo dyes with natural product-based compounds with multifunctional groups can increase the efficiency and probability of additional interactions with biological targets/receptors [3]. Our preliminary studies on azo dyes bearing natural product-based compounds such as aspirin and kojic acid showed antibacterial activities [3,8,9,10] and anticancer activity [11,12].…”
Section: Introductionmentioning
confidence: 79%
“…Among medicinal plants with interesting bioactive content, the genus Salix (willow) presents great potential, comprising about 500 species that grow well in marginal wet land distributed worldwide. This large number of species makes this plant one of the most abundant sources of renewable raw materials for multiple end-uses [3][4][5][6]. Willow extracts and herbal tea derived from the plant bark are currently available from the species S. purpurea, S. daphnoides, and S. fragilis [7].…”
Section: Introductionmentioning
confidence: 99%